Functional Outcome of Custom-Built Fixed Hinged Prosthesis for Tumors around the Knee. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: The determine the functional outcome of custom-built fixed hinged prosthesis for tumors around the knee.Methods: This descriptive study was conducted in  Department of Orthopedics & Spine Surgery Ghurki Trust Teaching Hospital Lahore from 3rd  January 2015 to 3rd January 2021.All adults patients of either gender and age with tumours of distal femur,proximal tibia or both fulfilling the inclusion criteria were operated for custom-built fixed hinged prosthesis.Post operative functional outcome was determined using Musculoskeletal Tumor Society(MSTS) system and results were graded as excellent(75-100%), moderate (70-74%), Good (60-69%), Fair(50-59%) and  Poor (